Changing Returns to Occupational Skill and Women's Wages - Felix Schran (Institute of Labor Economics (IZA), 2019)
This paper investigates to what extent changes in the returns to occupational skill and declining occupational segregation have reduced wage inequality between men and women. As a first pass, I find that roughly 65% of the decline in the gender wage gap between 1985 and 2010 can be explained by a reduction in occupational segregation between the genders. The remaining 35% are explained by shifts in occupational wages which increased within occupations important for female employment, and declined in many occupations important for male employment such as producing occupations. Motivated by the central of Böhm et al. (2019) that average wages do not move as much as skill prices, I reestimate the part of the declining wage gap attributed to changes in (selection corrected) skill prices. The impact of movements in skill prices on the reduction in gender wage inequality was roughly 13 percentage points larger than the impact of changes in average wages alone. Similar findings hold when decomposing the rise in the proportion of women at higher percentiles of the wage distribution and vice versa for lower percentiles. This underscores the importance of accounting for selection effects in decompositions.
Keywords: J16; J31; J24; 330; gender wage gap; inequality; Roy model; returns to skill; occupational choice